A DESCRIPTIVE STUDY ON FACTORS AFFECTING THE USE OF LEARNING APPROACH AMONG ACCOUNTING EDUCATION STUDENTS AT UNIVERSITAS NEGERI MEDAN - Sundari, Iis; Lianti, Lianti; Karima, Hidaya Tul; Triadiarti, Yulita; Siregar, Tapi Rumondang (Universitas Negeri Medan, 2020)
Understanding of learning material, especially accounting material, has an impact on the achievement of students' learning outcomes. The research aims to look at the factors that influence the learning approach of Unimed accounting education students. This research was carried out in the FE UNIMED using questionnaires distributed to students of the Accounting Education Program batch of 2015 and 2016, amounting 60 and 68 students from each batch. The selection of batches is based on the type of curriculum applied to each batch, namely the Indonesian National Qualification Framework (abbreviated as KKNI) for 2016 and the non-KKNI for 2015. The approach used in this study was a qualitative approach, with the analysis used was descriptive statistical analysis on factors such as interest, motivation, learning style, anxiety, institutional, and learning strategies. The descriptive analysis shows that except for the interest indicating that non-KKNI students have a higher interest in applying a variety of learning approaches of Non-KKNI students than their KKNI peers, other factors are similar between students from two batches. Keywords: Interest; Motivation; Learning Style; Anxiety; Institutional.